Respiratory Variation in Carotid Artery Peak Systolic Velocity Is Unable to Predict Fluid Responsiveness in Spontaneously Breathing Critically Ill Patients When Assessed by Novice Physician Sonologists. (August 2021) - Abbasi, Adeel; Nayeemuddin, Mohammed; Azab, Nader; Schick, Alexandra; Lopardo, Thomas; Phillips, Gary S.; Merchant, Roland C.; Levy, Mitchell M.; Blaivas, Michael; Corl, Keith A.
Background: Respiratory variation in carotid artery peak systolic velocity (ΔVpeak) assessed by point-of-care ultrasound (POCUS) has been proposed as a noninvasive means to predict fluid responsiveness. We aimed to evaluate the ability of carotid ΔVpeak as assessed by novice physician sonologists to predict fluid responsiveness. Methods: This study was conducted in 2 intensive care units. Spontaneously breathing, nonintubated patients with signs of volume depletion were included. Patients with atrial fibrillation/flutter, cardiogenic, obstructive or neurogenic shock, or those for whom further intravenous (IV) fluid administration would be harmful were excluded. Three novice physician sonologists were trained in POCUS assessment of carotid ΔVpeak. They assessed the carotid ΔVpeak in study participants prior to the administration of a 500 mL IV fluid bolus. Fluid responsiveness was defined as a ≥10% increase in cardiac index as measured using bioreactance. Results: Eighty-six participants were enrolled, 50 (58.1%) were fluid responders. Carotid ΔVpeak performed poorly at predicting fluid responsiveness. Test characteristics for the optimum carotid ΔVpeak of 8.0% were: area under the receiver operating curve = 0.61 (95% CI: 0.48-0.73), sensitivity = 72.0% (95% CI: 58.3-82.56), specificity = 50.0% (95% CI: 34.5-65.5). Conclusions: Novice physician sonologists using POCUS are unable to predict fluid responsiveness using carotid ΔVpeak. Until further research identifies key limiting factors, clinicians should use caution directing IV fluid resuscitation using carotid ΔVpeak.